Large-scale supervised learning For 3D point cloud labeling: Semantic3d. Net - Hackela, Timo; Wegnera, Jan D.; Savinov, Nikolay; Ladický, Ľubor; Schindler, Konrad; Pollefeys, Marc (Photogrammetric Engineering & Remote Sensing, 2018)
In this paper we review current state-of-the-art in 3D point cloud classification, present a new 3D point cloud classification benchmark data set of single scans with over four billion manually labelled points, and discuss first available results on the benchmark. Much of the stunning recent progress in 2D image interpretation can be attributed to the availability of large amounts of training data, which have enabled the (supervised) learning of deep neural networks. With the data set presented in this paper, we aim to boost the performance of CNNs also for 3D point cloud labelling. Our hope is that this will lead to a breakthrough of deep learning also for 3D (geo-)data. The semantic3D.net data set consists of dense point clouds acquired with static terrestrial laser scanners. It contains 8 semantic classes and covers a wide range of urban outdoor scenes, including churches, streets, railroad tracks, squares, villages, soccer fields and castles. We describe our labelling interface and show that, compared to those already available to the research community, our data set provides denser and more complete point clouds, with a much higher overall number of labelled points. We further provide descriptions of baseline methods and of the first independent submissions, which are indeed based on CNNs, and already show remarkable improvements over prior art. We hope that semantic3D.net will pave the way for deep learning in 3D point cloud analysis, and for 3D representation learning in general.